Effect of shell thickness of Pd core-porous SiO2 shell catalysts on direct synthesis of H2O2 from H-2 and O-2 - Seo, Myung-Gi; Kim, Ho Joong; Han, Sang Soo; Lee, Kwan-Young (ELSEVIER SCIENCE BV, 2017)
In our previous study, we applied Pd@SiO2 core-shell catalysts to hydrogen peroxide synthesis and obtained a higher yield of hydrogen peroxide than that obtained with the use of general supported catalysts (Pd/SiO2). As an extension of the previous study on Pd@SiO2 catalysts, the effects of the core-shell thickness on the hydrogen peroxide synthesis reaction were examined in this study. A shell below a certain thickness in the core-shell structure of the Pd nanocatalyst results in a decrease in the catalytic activity. Overall, a volcano curve is observed for the hydrogen peroxide production rate as a function of the shell thickness. Through N-2-adsorption and desorption, TEM, CO-chemisorption, and XRD analyses, we identify the causes for the improved direct hydrogen peroxide synthesis yields and later optimize the shell thickness for the efficient utilization of Pd. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: HYDROGEN-PEROXIDE SYNTHESIS; PD/SIO2 CATALYST; H-2-TO-H2O2 OXIDATION; AQUEOUS-MEDIUM; OXYGEN; NANOPARTICLES; HYDROCRACKING; DESTRUCTION; PALLADIUM; CHLORIDE